A remedy and a poison: perjury and trust in Bourbon Mexico. - Villa-Flores, Javier (Colonial Latin American Review, 2020)
The article outlines the relationship between oaths and testimonial competence in the inquisitorial system of justice. It mentions about the dangers posed by perjury, and pushed for the reformation of manners throughout Mexico; and establishing testimonial credibility, while emphasizing the crucial role played by judicial discretion (arbitrium) in the process. It mentions about the analysis of perjury cases tried by the Mexican Inquisition.